Exposure to Parental Alcohol Use Rather Than Parental Drinking Shapes Offspring's Alcohol Expectancies. (18th July 2019) - Smit, Koen; Voogt, Carmen; Otten, Roy; Kleinjan, Marloes; Kuntsche, Emmanuel
Abstract : Background: Alcohol expectancies (AE), that is, the anticipated effects of alcohol, start developing early in childhood and are important predictors of alcohol use years later. Whereas previous research has demonstrated that parental drinking relates to children's AE, this study aims to test whether exposure to parental alcohol use mediates the link between parental alcohol use and positive and negative AE among children (6 to 8 years) and early adolescents (12 to 15 years). Methods: Longitudinal multi‐informant family studies were conducted in the Netherlands among children (Study 1 (2015 to 2017): N =  329; 48.9% boys; M age  = 4.6) and adolescents (Study 2 [2015 to 2018]: N =  755; 45.6% boys; M age  = 11.3). Fathers' and mothers' alcohol use in terms of quantity and exposure (i.e., the frequency of alcohol use in 9 family‐specific situations), and offspring's AE were collected using online questionnaires. Results: Structural equation modeling conducted in the full sample and separately by gender revealed the following: For children, no associations were found in the full sample. However, gender‐specific results indicated that fathers' exposure was associated with (and mediated) favorable AE. Among adolescents, fathers' exposure was associated with (and mediated) social and coping AE (both boys and girls) and enhancement AE (only boys). Contrastingly, neither mothers' alcohol use nor its exposure was associated with any AE. Although different associations were found by offspring's gender, strong evidence for gender differences was lacking. Conclusions: This study indicates that, for specific expectancies, exposure to fathers' alcohol use shapes offspring's cognitions about the effects of alcohol, rather than fathers' alcohol use in general. Prevention efforts could focus on lowering the degree to which fathers expose their drinking, which might be more easily changeable than drinking in general. Abstract : This study examined whether exposure to parental alcohol use (offspring seeing their parents drinking) was associated with alcohol expectancies (AE), i.e., the anticipated effects of alcohol, among children (6 to 8 years) and early adolescents (12 to 15 years). Fathers' (but not mothers') exposure was associated with more positive AE (young girls), less negative AE (young boys) and social AE (adolescents) over and above fathers' alcohol use in general. Consequently, decreasing exposure to parental drinking might be an important goal for prevention efforts.